Potensi dan Tantangan Pemulung Menuju Ekonomi Sirkular di Kota Jambi - Mia Erpinda; Dwi Nowo Martono; Gabriel Andari Kristanto (Universitas Riau, 2023)
Waste pickers in Jambi city reduce solid waste by collecting and sorting recycled waste at the ‘Solid Waste Temporary Shelters’ or Tempat Pembuangan Sementara (TPS). However, most waste pickers cannot improve their performance due to challenges confronting waste pickers and lack of attention from the government and the public. This research identified and quantified the solid waste collected and marketed by individual waste pickers and collectors ‘pengepul’. Convenience sampling methods with literature reviews, questionnaires, and interviews were carried out in this study. Most respondents were male waste pickers, 67%, and women, 33% (n=100). The average daily collection rate of male waste pickers is 10.43 kg/day. For female waste, pickers are 7.92 kg/day (waste category: plastic bottles, cardboard, and wastepaper), with an estimated recycling rate of 0.09%-0.89%. Meanwhile, collectors have an average sales rate of 2-5.5 tons/month, with an estimated recycling rate of 1.5%. The recycling value of waste pickers and collectors could be more optimal, impacting the average income of waste pickers Rp. 581,250/month which showed that the market is neither profitable nor socially protected. The research findings could help develop a waste pickers' integrated system to improve the implementation of the circular economy.